PEMBENIHAN IKAN KERAPU TIKUS (Cromileptes altivelis) DI BALAI PERIKANAN BUDIDAYA AIR PAYAU SITUBONDO - Imam Prayogo; Farid Hidayat (Samakia : Jurnal Ilmu Perikanan, 2014)
This research was conducted at the Center for Brackish Water Aquaculture Situbondo on February to April 2013. The research material is the development of the egg mouse grouper (Cromileptes altivelis) to the size of the seed. Humpback grouper hatchery activities undertaken in Situbondo Brackish Water Aquaculture Centres covering, container preparation, maintenance of the parent, the parent spawning, handlers egg, larva, natural food culture, water quality management and harvest seeds. Spawning parent process carried out at the bright moon and new moon after the management maintained a predetermined feed. Observations eggs done from the early morning (eggs age ± 4 hours) to hatch (± 28 hours) by using a light microscope with a magnification of 10 x10. Larval rearing is to obtain seeds produced optimally usual during 45-55 days. The seeds that will harvest measuring 2 hinga 5 cm and ready to send to consumers first fasted for between 12-24 hours with the aim of reducing expenditure stool (feces) during transport seeds.